PENGARUH LKS BERBASIS KETERAMPILAN BERPIKIR KREATIF DALAM STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KOMPETENSI SISWA KELAS VIII SMP ADABIAH KOTA PADANG - Vonny Tinedi; Djusmaini Djamas; Ratnawulan Ratnawulan (Universitas Negeri Padang, 2015)
The low of students’ competence in Natural Science is due to the lack of learning step that sharpen students creativity in teaching materials. Students’ creativity can be sharpened by using problem based learning strategy and students worksheet based on creative thinking skill. Therefore, the purposes of this research is to inquire the influence of students worksheet based on creative thinking skill in problem based learning strategy toward eight grade students competence at Adabiah junior high school. This research used quasi experiment research type and randomized control group pretest-posttest design. The population of this research was all students of Adabiah junior high school in eight grade of academic year 2014/2015. The research instruments were test sheet for knowledge competence, score rubric of creative thinking, score rubric for skill competence, and students worksheet based on creative thinking skill. The result of this research showed that the mean score of knowledge and skill competence in experimental class was higher than control class. However, the result of statistical analysis showed that there was no significance difference between both competence in both class sample at 0,05 significance level. Thus, the use of students worksheet based on creative thinking skill in problem based learning strategy has not yet been able to improve students’ knowledge and skill competence